A Chemical Perspective on Transcriptional Fidelity: Dominant Contributions of Sugar Integrity Revealed by Unlocked Nucleic Acids1. Issue 47 (24th October 2013) - Xu, Liang; Plouffe, Steven W.; Chong, Jenny; Wengel, Jesper; Wang, Dong
<x xml:space="preserve">Abstract</x> Transcription unlocked: A synthetic chemical biology approach involving unlocked nucleic acids was used to dissect the contribution of sugar backbone integrity to the RNA Polymerase II (Pol II) transcription process. An unexpected dominant role for sugar‐ring integrity in Pol II transcriptional efficiency and fidelity was revealed.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>